Thoughts on Construction Risk Mitigation and Acceptance. Issue 1 (2nd January 2018) - Tanner, Peter; Hingorani, Ramon; Bellod, Juan Luis; Sanz, David
Abstract: Civil construction is a highly uncertain endeavour that entails a considerable risk, as attested to by the succession of incidents and accidents reported the world over. The reasons for this situation need to be identified before strategies can be adopted with a view of reducing the construction-related risks. Taking the forensic investigations of a series of accidents as a starting point, this article explores the generally applicable lessons learnt from those case studies. Such surveys show that the problems to be dealt with in everyday practice are rather elementary and often attributable to human error. Basic principles and recommendations are therefore put forward for the design, erection and use of temporary structures in general and ancillary equipment for construction processes in particular, aimed at reducing the risks associated with such activities. Moreover, as there is no general consensus on reliability requirements for the temporary structures, this paper addresses the establishment of acceptable life safety risk and the associated reliability levels. The requirements put forward aim to ensure the same statistical fatality rate per unit of time as for the permanent structures. The effect of the established principles, recommendations and requirements on the design and assembly of the temporary structures is illustrated by means of an example.